DEVELOPMENT OF ATTENTION PROPERTIES IN PRESCHOOL CHILDREN BY MEANS OF GAME TECHNIQUES - Patrul, Mariia; Kuzmych, Oleksandra (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The presents the results of a theoretical analysis of the properties of attention and an empirical study of the development of preschoolers’ attention properties by means of game techniques. The purpose of the study is to theoretically analyse and empirically investigate the peculiarities of the development of preschoolers’ attention properties, to develop and implement a correctional programme for the development of preschoolers’ attention properties using game techniques. The research procedure was based on a set of theoretical, empirical and statistical research methods. The theoretical study used theoretical and methodological analysis, synthesis of comparison, systematisation and generalisation of scientific literature on the problem of studying the properties of attention. At the stage of empirical research, observations, interviews, testing, and an experiment, which included a statement and a formative part, were used. At the stages of the establishing and formative experiments, special psychodiagnostic techniques were used: to diagnose the properties of attention in preschool children - “Pieron-Rooser Test” to determine the level of concentration of attention; “Bourdon’s Correctional Test” to determine the level of attention stability; “Find and Count Shapes” technique to determine the level of attention span. The experimentally obtained data were processed using mathematical statistics methods: the Kolmogorov-Smirnov test to determine the type of data distribution, group comparison method (Mann-Whitney U to compare two independent samples). The results. In the course of empirical research of preschoolers’ attention properties development by means of game techniques, high levels of attention properties were revealed by the following indicators: concentration of attention - 50% of respondents; attention stability - 45%; attention volume - 55%. Medium levels: concentration - 40% of respondents; sustainability - 45%; volume - 35%. Low levels of attention properties: concentration - 10%; sustainability - 45%, volume - 10%. Thus, the next stage was the creation and implementation of a correctional programme for the development of attention properties using game techniques. Also, the effectiveness of the developed correctional development programme was evaluated using mathematical data processing. Based on the results of the study, a conclusion was made about the effectiveness of the correctional programme for the development of attention properties using game techniques and recommended for use in the work of practical psychologists in preschool education institutions